Cross-sectional Survey of Long-Term Care Facilities in the Rockaway Peninsula: Preparedness and Response During Hurricane Sandy. (14th August 2017) - Jiang, Lynn; Tedeschi, Christopher; Subaiya, Saleena
Abstract: Background: Few studies have described the challenges experienced by long-term care facilities (LTCFs) following Hurricane Sandy. This study examined LTCF preparedness and experiences during and after the storm. Methods: A cross-sectional survey was conducted 2 years after Hurricane Sandy to assess LTCF demographics, preparation, and post-storm resources. Surveys were conducted at LTCFs located on the Rockaway Peninsula of New York City. All LTCFs located in a heavily affected area were approached. Results: Of 29 facilities, 1 had closed, 5 did not respond, 9 declined to participate, and 14 participated, yielding a response rate of 50% for open facilities. Twenty-one percent of the facilities had preparations specifically for hurricanes. More than 70% of the facilities had lost electricity, heat, and telephone service, and one-half had evacuated. Twenty-one percent of the facilities reported not receiving any assistance and over one-half reported that relief resources did not meet their needs. Conclusions: Many LTCFs lacked plans specific to such a large-scale event. Since nearly all of the LTCFs in the region were affected, preexisting transportation and housing plans may have been inadequate. Future preparation could include hazard-specific planning and reliance on resources from a wider geographic area. Access to electricity emerged as a top priority. ( Disaster Med Public Health Preparedness . 2018;12:194–200)